Targeted bile acid profiles reveal the liver injury amelioration of Da-Chai-Hu decoction against ANIT- and BDL-induced cholestasis - Zhou, YueHua; Zhou, YunZhong; Li, YiFei; Sun, Wei; Wang, ZhaoLong; Chen, Long; He, Ye; Niu, XiaoLong; Chen, Jialiang; Yao, Guangtao (Frontiers in Pharmacology, 2022)
Multiple types of liver diseases particularly cholestatic liver diseases (CSLD) and biliary diseases can disturb the bile acids (BAs) secretion, however BAs accumulation is currently seen as an important incentive of various types of liver diseases progression. Da-Chai-Hu Decoction (DCHD) has long been applicated for treating cholestatic liver diseases, however the exact mechanisms remain unclear. Currently, our study indicates that the liver damage and cholestasis status of the α-naphthylisothiocyanate (ANIT)-induced intrahepatic cholestasis and bile duct ligation (BDL)-induced extrahepatic cholestasis following DCHD treatment were improved, the changes of BAs metabolism post DCHD treatment were investigated using targeted metabolomics profiling by UPLC-MS/MS. DCHD treatment severely downregulated serum biochemical levels and relieved inflammation and the corresponding pathological changes including necrosis, inflammatory infiltration, ductular proliferation and periductal fibrosis in liver tissue. The experimental results suggested that DCHD treatment altered the size, composition and distribution of BAs pool, led the BAs pool of the serum and liver sharply shrink especially TCA and TMCA, and enhanced BAs secretion into the gallbladder and the excretion of BAs by urinary and fecal pathway, the levels of BAs synthesized by alternative pathway were increased in liver, the conjugation of BAs and the pathway of BAs synthesis were actually affected. In conclusion, DCHD ameliorated ANIT and BDL-induced cholestatic liver injury by reversing the disorder of BAs profiles.